Positional comparison of jump performance in NCAA division I female volleyball athletes - Rush, M. E.; Littlefield, T.; McInnis, K. A.; Denahue, P. T. (International Journal of Kinesiology & Sports Science, 2022)
Background: The vertical jump task is a critical component of success in volleyball. Each position on the court has its own physical demands and has differing levels of vertical jump task demands. Objective: Thus, the objective of this investigation was to compare vertical jump performance between the two positional groups using the countermovement jump (CMJ) and squat jump (SJ). Methods: Using an observational cross-sectional study design, nineteen NCAA Division I female volleyball athletes participated in this investigation. Participants first performed three CMJ trials followed by 3 SJ trials on a force platform. Jump height, peak and mean net propulsive forces, and time to take off were calculated for both the CMJ and SJ. Reactive strength index modified and propulsive duration were additionally calculated for the CMJ and average RFD for the SJ. Independent sample t-tests were performed comparing positional groups on each variable of interest with Hedges g effect sizes additionally calculated. Results: No statistically significant differences (p < 0.05) were found between any of the variables of interest in the CMJ though moderate effect sizes were seen in jump height (g =0.78). No statistically significant differences were present in the SJ though moderate effect sizes were seen in RFD (g = 0.65), mean propulsive force (g = 0.79) and peak propulsive force (g = 0.66). Discussion: As the vertical jump task is a critical task for high-level performance in both positions, and the no differences seen between groups, training programs should be designed to improve jump performance with special attention to the individual athletes` needs rather than the specifics of the playing position.